2017
DOI: 10.22521/edupij.2017.62.4
|View full text |Cite
|
Sign up to set email alerts
|

Factors and Predictors of International Student’s Satisfaction in Turkey

Abstract: Satisfaction of student has been viewed as a vital factor regarding quality of learning approach and a key factor in the success of learning programs. The purpose of this paper is to investigate how students perceive the environment, quality, and services they are offered at a Turkish university and how satisfied they are with them. The analysis utilized structured questionnaire and use SPSS for determining correlation among different factors of satisfaction. Also it applied step wise multiple regression to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Therefore, it is necessary to know the perceptions of the students about the services provided by the institutions in order to understand the satisfaction and experience of them. Knowing the factors affecting student satisfaction is vital for the institution concerned with student expectation (Uddin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is necessary to know the perceptions of the students about the services provided by the institutions in order to understand the satisfaction and experience of them. Knowing the factors affecting student satisfaction is vital for the institution concerned with student expectation (Uddin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there are many researches that had focused on measuring students' satisfaction (Elliott and Shin, 2002;Price ., 2000;Uddin ., 2017). This measurement instrument consisting of 50 questions was developed by last year chemical engineering department student under the supervision of a teaching member to get students' opinions about the teaching program and the university they are studying.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some participants mentioned having academic support with courses and thesis processes; however, others stated some concerns about course content which was designed for domestic students and overlooked international students' needs. In another study, researchers investigated factors to determine international students' overall satisfaction of their experience in Turkey and results indicated that quality of education, and administrative staff support were the top two significant factors on students' satisfaction (Uddin, Mamun, Soumana, & Khan, 2017). Further, researchers stated that campus environment and safety, self-preparation, personal influence as recommendations given by family or friends were also found to be related to students' satisfaction.…”
Section: College Adjustment Among International Students In Turkeymentioning
confidence: 99%
“…service receivers in the public sector (Kim et al, 2018) patients in clinics (Bible et al, 2018) employees in business organizations (Samani et al, 2018) customers using mobile banking applications (Al-Otaibi et al, 2018) patients in emergency units (Chang et al, 2018) tourists visiting tourism destinations (Pawaskar and Goel, 2017) students of universities (Uddin et al, 2017) and customers mobile telecommunication companies (Lai and Nguyen, 2017). Since the interest of the current study is limited to the satisfaction of tourists, the following sections relate to this type of satisfaction only.…”
Section:  Tourist Satisfaction Dimensionsmentioning
confidence: 99%